Representasi Amangkurat I dalam Babad Tanah Jawi Terjemahan W. L. Olthof dan Novel Amangkurat Karya Ardian Kresna - Joko Sujarwo; Nur Fatul Aini; Dwi Susanto (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
There is a difference in the depiction of Amangkurat I in the Babad Tanah Jawi (2008) and the novel Amangkurat (2012). The discussion on the figure of Amangkurat I, specifically in recent studies, has not been widely discussed. The purpose of this study is to determine the representation of the figure of Amangkurat I in both works. This research includes a qualitative-descriptive study. The data used are in the form of text content in both literary works, the author's background, discourse on character representation, and sociology of literature. Interpretation of data is carried out in accordance with the workings of the theory of sociology of literature. The results of the research show that there is a more positive impression of the image of Amangkurat I, when compared to the novel, which appears in the babad story. This impression appeared in several events, namely the early period after the coronation, the construction of the Plered palace, the death of the Mataram tumenggung, the death of the Queen of Malang, the gift of bekisar by Prince Pekik, and the escape to Betawi. Such a narrative in the Babad Tanah Jawi can be assumed as an effort to legitimize the authorities. Then, the different depictions that appear in Amangkurat's novel show the author's partiality towards Dutch records against the story in Babad Tanah Jawi. Thus, the presence of the novel Amangkurat can be interpreted as a reaction or response by Ardian Kresna to the story in the Babad Tanah Jawi. Keywords: Representation, Amangkurat I, Babad Tanah Jawi, Amangkurat’s novel